PENINGKATAN PENGAWASAN GURU AGAMA HINDU DALAM MENGHADAPI PROBLEMATIKA PENDIDIKAN DI KEMENTERIAN AGAMA KOTA DENPASAR - Ni Wayan Sukerti (Guna Widya: Jurnal Pendidikan Hindu, 2018)
The obstacles that arise in the implementation of the Hindu Religious Education supervisor program is one of the obstacles in the field of education, especially in Hindu Religious Education, so the need for efforts made by the Superintendent of Hindu Religious Education to overcome these obstacles. Efforts to overcome ob- stacles in the field of education is a necessity to always be implemented so that the quality of education can be improved, developed and developed. Efforts by supervisors to overcome obstacles to supervisory program implementation lead to the construction process. Supervisors of Hindu Religious Education will try to build, give encouragement to the teacher and himself to carry out the task well, so as to improve its performance.